Refleksyjność studentów pedagogiki - Perkowska-Klejman, Anna (Wydawnictwo Naukowe UAM, 2016)
The study investigates the development of reflective thinking by undergraduate and postgraduate pedagogy students. The theoretical foundation is based on Dewey’s, Mezirow’s and Magolda’s reflection construct. Based on these theories, Kember theorized that reflective thinking may be categorised into four distinct stages: habitual action, understanding, reflection, and critical reflection. A reflective thinking questionnaire was completed by 300 students from a Pedagogy Faculty. Participants were first-year undergraduate, third-year undergraduate and second-year postgraduate university students. The Anova test found significant differences in scores for understanding and critical reflection.
Pedagogy Students’ Reflexivity
Keywords: reflective thinking; transformative thinking; reflection questionnaire; cognitive development